Pengaruh Iklim Organisasi dan Motivasi Kepala Madrasah Terhadap Kinerja Guru - Ayu Asmarani; Muhammad Fadhil; Darma Putra (Journal of Educational Research, 2022)
This study aims to analyze the effect of organizational climate variables and the motivation of the madrasa principal on teacher performance. This research is a quantitative research with a survey approach that was conducted in Madrasah Aliyah Negeri in Batang Hari Regency, Jambi Province. The research population is the teachers of the State Madrasah Aliyah in Batang Hari Regency. The sampling technique used random sampling technique with a total sample of 61 teachers. The data were analyzed by multiple linear regression, and processed with the help of the SPSS Version 20 program. The results showed; (1) there is a significant influence between organizational climate on teacher performance. (2) there is a significant influence between the motivation of the madrasa principal on teacher performance. (3) there is a significant effect between the organizational climate and the motivation of the madrasa principal simultaneously on teacher performance. Where if the organizational climate and motivation of the madrasa principal is getting better, the performance of the Madrasah Aliyah Negeri teachers in Batang Hari Regency, Jambi Province will also be better. Penelitian ini bertujuan untuk menganalisis pengaruh antara variabel iklim organisasi dan motivasi kepala madrasah terhadap kinerja guru. Penelitian ini adalah penelitian kuantitatif dengan jenis pendekatan survei yang dilakukan di Madrasah Aliyah Negeri di Kabupaten Batang Hari Provinsi Jambi. Populasi penelitian adalah guru Madrasah Aliyah Negeri di Kabupaten Batang Hari. Teknik penarikan sampel menggunakan teknik random sampling dengan jumlah sampel penelitian sebanyak 61 guru. Data dianalisis dengan regresi linear berganda, dan diolah dengan bantuan program SPSS Versi 20. Hasil penelitian menunjukkan; (1) terdapat pengaruh signifikan antara iklim organisasi terhadap kinerja guru. (2) terdapat pengaruh signifikan antara motivasi kepala madrasah terhadap kinerja guru. (3) terdapat pengaruh signifikan antara iklim organisasi dan motivasi kepala madrasah secara simultan terhadap kinerja guru. Dimana apabila iklim organisasi dan motivasi kepala madrasah semakin baik maka akan semakin baik pula kinerja guru Madrasah Aliyah Negeri di Kabupaten Batang Hari Provinsi Jambi.